Recruiting Small Manufacturing Worksites That Employ Multiethnic, Low-wage Workforces Into a Cancer Prevention Research Trial - Elizabeth M. Barbeau; Lorraine Wallace; Ruth Lederman; Nancy Lightman; Anne Stoddard; Glorian Sorensen (Centers for Disease Control and Prevention, 2004)
Introduction Worksites, including those that employ multiethnic, low-wage workforces, represent a strategic venue for reaching populations at risk for developing cancer. Methods We surveyed 197 small manufacturing worksites prior to an effort to recruit their workforces into a randomized clinical trial designed to test the effectiveness of a cancer prevention intervention among multiethnic, low-wage manufacturing workers. This paper assesses the external validity of the trial based on three factors: the percentage of potential trial sites excluded from consideration, the percentage of eligible worksites that adopted the trial, and worksite characteristics associated with adoption. Results We found no statistically significant differences between worksites that adopted the trial and worksites that declined the trial with regard to employee demographics, anticipated changes in workforce size, and perceived importance and history of offering health promotion and occupational health and safety activities. Conclusion Small manufacturing worksites present a viable venue for reaching multiethnic, low-wage populations with cancer prevention programs, although program adoption rates may be low in this sector. Worksites that adopted the trial are likely to represent worksites deemed eligible for the trial.